2016
DOI: 10.2174/1874312901610010122
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MDA5 Antibody Dermatomyositis Overlap with Systemic Lupus Erythematosus: A Case Report and Review of the Literature

Abstract: Background:Dermatomyositis (DM) is an autoimmune connective tissue disease that primarily targets the muscle, skin, and lungs. Many patients have autoantibodies that correspond to distinct clinical phenotypes. Melanoma differentiation-associated gene 5 (anti-MDA5) antibody, a specific antibody that targets the melanoma differentiation-associated gene 5 (MDA5), has been reported in DM cases and is significant for a distinct cutaneous presentation and rapidly progressive interstitial lung disease.Objective:Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…As the hypomethylation of SLE-related genes promoters had unique effects on the activation of the dysfunction of immune systems in SLE, so we suggested hypomethylation level of MDA5 promoter might also activate the abnormal immune responses in SLE. It has been shown that MDA5 could be induced in human mesangial cells, and it was detectable in patients with severe lupus nephritis, 16 our results confirmed that MDA5 expression in patients with lupus nephritis was significant higher. As dsDNA antibody reflects the activity of SLE and the involvement of lupus nephritis, and our results demonstrated patients with dsDNA(+) had higher level of MDA5.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As the hypomethylation of SLE-related genes promoters had unique effects on the activation of the dysfunction of immune systems in SLE, so we suggested hypomethylation level of MDA5 promoter might also activate the abnormal immune responses in SLE. It has been shown that MDA5 could be induced in human mesangial cells, and it was detectable in patients with severe lupus nephritis, 16 our results confirmed that MDA5 expression in patients with lupus nephritis was significant higher. As dsDNA antibody reflects the activity of SLE and the involvement of lupus nephritis, and our results demonstrated patients with dsDNA(+) had higher level of MDA5.…”
Section: Discussionsupporting
confidence: 87%
“…Milam once reported a patient with a positive anti-MDA5 antibody, who subsequently developed coexisting SLE. 16 More importantly, DM is known to overlap with other connective tissue diseases (CTD), such as SLE, so we supposed MDA5 might be involved in the development of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…On retesting, all antiphospholipid antibodies were negative. Therefore, consistent with previous reports, a skin biopsy lacking evidence of vasculitis or thrombotic vasculopathy, and a great response to IVIG, we report a not so common overlap presentation of necrotic skin lesions driven by MDA‐5 in lupus (2).…”
supporting
confidence: 92%
“…Melanoma differentiation–associated gene 5 (MDA‐5) is associated with dermatomyositis and often presents with a distinct cutaneous presentation and progressive interstitial lung disease (ILD) (1–3). MDA‐5 signaling often leads to increased interferon signaling, which contributes to atypical vasculopathy, leading to atypical, and at times ulcerative or necrotic, cutaneous manifestations, which are challenging to diagnose and treat (2). Rarely, patients with lupus present with necrotic skin lesions as an overlapping presentation from MDA‐5 dermatomyositis.…”
mentioning
confidence: 99%
“…Interestingly, MDA5 showed the highest prevalence in the control population, including two SLE patients and one individual with infectious disease. Overlap cases of MDA5 associated CADM and SLE have been previously described [ 40 ]. Whether the reactivity in the ID patient represents a pathogenic mechanism as discussed previously deserved further research [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%